Holistic Education: A Catalyst for Actualizing Sustainable Development Goals in Primary School Curricula - Folasade Esther Jimola; Graceful Onovughe Ofodu (Scientia Publica Media, 2025)
Education begins the day a child is born to the time of death. Inculcating the right attitude and perception about sustaining development goals (SDGs) should start in earnest, immediately after a child is born. Primary education is crucial to achieving SDGs and serves as the bedrock that determines the sustainability of other levels of education. Holistic education at the primary level is an indispensable factor that can help implement and achieve all 17 sustainable development agenda. This paper: i) enumerates the benefits of teaching SDGs at primary level of education, ii) reveals the constraints bedeviling the actualization of SDGs at the primary level of education, iii) demystifies the integration and application of holistic pedagogy in teaching and learning of sustainability in lesson content, iv) introduces holistic strategies as effective means of teaching SDGs (1, 2, 3, 5, 6, 13, 14, 15, and 16), v) explains how and why holistic education is a lynch pin to the actualization of SDGs, vi) shows how to incorporate informal education into formal education in primary schools for sustainable development, and vii) presents language mix as a viable means to achieving SDGs. The paper concludes that to meet the 2030 SDGs agenda, primary education needs to prioritize: acquisition of sustainable development (SD) contents in classrooms; learning of SD-related skills; application of SDGs to life situations; inculcation of values and right attitudes towards SDGs; and utilization of learner-centred techniques in teaching and learning of SD topics. It was recommended that primary school teachers should expose pupils to holistic education that covers philosophical, social, environmental, economic, and emotional aspects, and pedagogical practices, rather than solely prioritizing the academic aspect for examination purposes.